Association of hepatic steatosis and liver fibrosis with chronic obstructive pulmonary disease among adults - Dayang Zheng; Xiang Liu; Wei Zeng; Wangyan Zhou; Chunxiang Zhou (Scientific Reports)
Abstract With high prevalence and substantial mortality, metabolic dysfunction-associated steatotic liver disease and chronic obstructive pulmonary disease (COPD) are significant public health concerns. Utilizing a large, population-based dataset from the National Health and Nutrition Examination Survey, our study probes the relationship between COPD prevalence and hepatic steatosis and fibrosis, as measured by Vibration-Controlled Transient Elastography. We analyzed data from 693 individuals with COPD and 7229 without. Through weighted multivariate logistic regression analysis, a restricted cubic spline curve, and threshold effect analysis, we investigated the correlation between the severity of hepatic steatosis and fibrosis and the presence of COPD. Our findings revealed a positive correlation between the controlled attenuation parameter (CAP) and COPD prevalence [OR = 1.03 (95% CI 1.01, 1.05)], even after multivariate adjustment. Furthermore, we observed a U-shaped association between CAP and COPD, where the inflection point, CAP value of 264.85 dB/m, corresponded to the lowest COPD prevalence. Our study emphasizes a substantial and complex link between hepatic steatosis and COPD. These findings urge healthcare professionals to factor liver health into COPD management and prompt further exploration into the underlying mechanisms. This could pave the way for the development of improved prevention and treatment strategies.